The Relationship Between Workload and Burnout Incidence in Nurses in Critical Care Room: The Relationship Between Workload and Burnout Incidence in Nurses in Critical Care Room X Hospital Bekasi City - Angraini, Arindra Dwi; Sapeni, Muhammad Al Amin R.; Lastriyanti, Lastriyanti (An Idea Health Journal, 2023)
The high workload that nurses have in critical care rooms can cause burnout events that impact not only nurses, but also patients and hospitals. Based on global data in 2020, nurses who experience the highest burnout work in intensive & critical care rooms at 14.36%. This type of research is descriptive research with a quantitative approach with a cross sectional research design. Data collection was carried out using the NASA-TLX Workload measurement questionnaire and the MBI Burnout measurement questionnaire (Maslach Burnout Inventory) for 84 nurses in the critical care room of Hospital X Kota Bekasi. Data were analyzed using SPSS with Chi-square test. The results of this study indicate that there is no relationship between workload and burnout events in nurses in the Critical Care Room at Hospital X Bekasi City which is indicated by a significance value (p-value) of 0.580 (? > 0.05) and has a very weak relationship indicated by a correlation coefficient of 0.088. It was concluded that workload was not related to the incidence of burnout in nurses in the Critical Care Room of Hospital X Bekasi City.